Biểu diễn tự động ảnh đường nét - Kiem, Hoang; Ky, Nguyen Ngoc (Journal of Computer Science and Cybernetics, 2018)
This paper presents the methods of automatic representation of digital lines. Both approaches sklettisation and contour following have been considered and evalued.